Bioinformatics and Immune Infiltration Analyses Reveal the Key Pathway and Immune Cells in the Pathogenesis of Hypertrophic Cardiomyopathy - Zhang, Xu-Zhe; Zhang, Si; Tang, Ting-Ting; Cheng, Xiang (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study was designed to identify key pathway and immune cells for hypertrophic cardiomyopathy (HCM) via bioinformatics analyses of public datasets and evaluate the significance of immune infiltration in the pathogenesis of HCM. Methods: Expressional profiling from two public datasets (GSE36961 and GSE141910) of human HCM and healthy control cardiac tissues were obtained from the GEO database. After data preprocessing, differentially expressed genes (DEGs) were then screened between HCM and healthy control cardiac tissues parallelly. Gene ontology, pathway functional enrichment and gene set enrichment analysis were performed using DAVID and GSEA application. The compositional patterns of immune and stromal cells in HCM and control cardiac tissues were estimated based on the merged data using xCell. Protein-protein interaction (PPI) network and module analyses were constructed by STRING and Cytoscape applications. Gender-based expressional differences analyses were also conducted to explore gender differences in HCM. GSE130036 and clinical samples were used for verification analyses. Results: A total of 308 DEGs were identified. Up-regulated DEGs mainly enriched in “adhesion” and “apoptotic process” in biological process. As for the down-regulated DEGs, “inflammatory response”, “innate immune response”, “phagosome” and “JAK-STAT signaling pathway” were highly enriched. Immune infiltration analyses suggested the scores of macrophages, monocytes, DC, Th1, Treg and plasma cells in HCM group were significantly decreased, while CD8+T cells, basophils, fibroblasts and platelets were significantly enriched. Module analyses revealed STAT3, as the hub genes in HCM together with LYVE1+CD163+ macrophages may play a key role in the pathogenesis of HCM while there were no obvious gender differences in the HCM samples from selected datasets. Verification analyses performing on GSE130036 and clinical samples showed a strong positive correlation (Pearson’s correlation=0.77) and a well co-localization relationship between LYVE1 and CD163, suggesting the potential function of LYVE1+CD163+ macrophages in maintaining the homeostasis of cardiac tissue. Conclusion: STAT3-related pathway and CD163+LYVE1+ macrophages were identified as the potential key pathway and immune cells in HCM and may serve as interesting targets for further deepening research.